African Family Support Systems and Psychological Wellbeing of the Ageing People in Nso of the Northwest Region of Cameroon - Kiywo, Ngalim Nestor (Journal of Innovation in Education and Social Research, 2024)
This study examined African family support systems and their influence on the psychological well-being of the ageing in Nso of the North-West Region of Cameroon. The eroding psychological well-being of the ageing persons in Nso is disturbing thus the need to explore how it could be revamped through appropriate Africentric social support systems. The concurrent-nested research design was used in conducting the study whereby the qualitative data was nested to add more value to the quantitative data. A sample of 175 (one hundred and seventy-five) was chosen from purposefully selected three rural areas and one urban area. Data were analysed using both descriptive and inferential statistics as well as via content thematic analysis for qualitative data. Based on family social support systems, finding showed that 60.6 % (1060) often and 18.0% (315) always experience family social support system. All three background variables (settlement type, sex, and marital status) were significantly predictive elements on traditional counselling support system with a significant ratio of 0.001. There is a significant, positive, and strong influence between family social support systemship and hedonic well-being. Family and societal relationships were identified as various media of interactions between the old people and the young. These family social support systems happen via the immediate family, extended family, rites of passage and cultural festivals. Because aspects of these family social support system do not portray the same weight as evident in the findings, it is recommended that more attention be focused on the young handling the hygienic aspect of the old and agrarian activities better while the opportunity for the old to attend traditional ceremonies in the company of the young be upheld as has been the case. In this regard, the well-being of the old will hopefully be ensured in its true nature.